A Study On Outbreak Of Blue Tongue Disease In Livestock Of Erode District Of Tamilnadu - Yasothai , R.; Shamsudeen, P. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Blue tongue is one of the most important arthropod borne infectious diseases of sheep in Southern India (Sreenivasulu and Subba Rao, 1999). It is caused by a RNA containing Orbivirus of Reoviridae family. Twenty four antigenic strains of the virus have been identified, which vary in their pathogenicity. It spreads through blood sucking midges of the genus Culicoides and is more pronounced during the monsoon season when the vector population is more (Wilson Aruni et al., 1999). Factors such as unrestricted animal movement, rain fall, geographical location, and multiple serotypes have made the control of the disease difficult (Shasidhar et al., 1998). In Tamil Nadu, Erode District ranks first in total sheep population and outbreak of any disease in sheep causes severe economic loss to the livestock farmers of the district. Hence information on the season of the disease occurrence, area and species most affected by blue tongue based on previous outbreaks are very useful for the disease forecasting. The present study deals with an epidemiological pattern of blue tongue in Erode District of Tamil Nadu.